Concise history of the Indian economy 1750 -1950 - "Bhattacharyya, Dhires" (New Delhi, 1979)
This book is simple introduction to the important economic events of this period. This book covers the following topics Trade under the east India company;The economic drain from India; Revenue administration under the east India company; Economic transition in India; Famines and famine relief; Agriculture and agricultural policy under British rule; state and to industry; History of modern industrial development; Industrial organisation, entrepreneurship and capital; History of India's foreign trade and trade policies; Transport and communications; Labour legislation and the trade union movement; History of Indian currency; Banking development in India;Government finance; National income levels of living and price movements etc.
Keywords: Economics